2006
DOI: 10.1080/02841850600796517
|View full text |Cite
|
Sign up to set email alerts
|

Static bone cavity of the mandible: computed tomography findings with histopathologic correlation

Abstract: Contrast enhancement of the soft tissue on the contrast-enhanced CT images suggests the presence of vasculature in the cavities. Histopathological examination confirmed the presence of fatty tissue and dilated abnormal vessels, and the absence of salivary gland tissue in the cavities. These findings show that vascular structures are prominent in tissues found in static bone cavities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
1
10
0
7
Order By: Relevance
“…However, they did not suggest any possible cause for the ischaemia. In recent times, Minowa et al 7,8,22 suggested that bone erosion due to an acquired vascular lesion is another possible explanation for the formation of SBD of the mandible. According to them, the facial artery and its branches can become tortuous owing to hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they did not suggest any possible cause for the ischaemia. In recent times, Minowa et al 7,8,22 suggested that bone erosion due to an acquired vascular lesion is another possible explanation for the formation of SBD of the mandible. According to them, the facial artery and its branches can become tortuous owing to hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…1 Many other terms have been used to describe this entity, including aberrant or ectopic salivary gland; static, latent or idiopathic defect, cavity or cyst; mandibular salivary gland inclusion; lingual mandibular bone cavity, concavity or depression; and Stafne cyst, defect or cavity. [2][3][4][5][6][7][8][9][10][11] The posterior lingual variant has an incidence of between 0.10% and 0.48% when diagnosed radiologically. However, some cadaver studies have revealed that the incidence of the lesion may be as high as 6.06%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10] Moreover, computed tomography (CT) findings with histopathologic correlation demonstrated that the contents of the static bone cavity were vascular structure and fat tissue without the gland. 11 The clinical symptoms of a static bone cavity are not remarkable and the causes of the static bone cavity are still not completely established. Although no treatment is required for patients with static bone cavity of the posterior mandible for an excellent prognosis, a biopsy may be necessary to rule out other pathological lesions in the static bone cavity of the anterior mandible and enlargement case.…”
Section: Introductionmentioning
confidence: 99%
“…Although the number of reports continues to accumulate, knowledge about the aetiology and pathogenesis of SBD has been limited and confusing for a long time. 3,[7][8][9][10] Although the radiological features of SBD have been widely reported, the use of cone beam CT (CBCT) for its diagnosis has been rarely reported. 11 The aim of this article is to clarify the frequency of this phenomenon by using multi-slice CT (MSCT) and CBCT to add to our understanding of the aetiology and content of SBDs by MSCT analysis, and to investigate CBCT use as a tool for exploring SBDs…”
Section: Introductionmentioning
confidence: 99%